PSYCHOLINGUISTICS: BILINGUALISM AND ITS EFFECTS ON CHILDREN THINKING - Purba, Rahel Sastri; Damanik, Bernieke (Cahaya Ilmu Bangsa Institute, 2025)
The aim of this study research to examine the established children, by acquire languages at the early age and this study focus on the scientific of human mind and human language, human mind it is mental action that acquire knowledge of understanding. Especially at children’s it’s known as psycholinguistics where the language acquisition child use in two different languages at the same time or usually is known as bilingualism first language acquisition. Basically, the search study purpose to analyses about language and human mind, and the topic it’s about bilingualism and its effects on thinking at the early age of children’s acquisition, that are concentrate as a central issue in this fields. This research method is useful for guiding researchers views in the research conducted. This research was conducted with the aim of describing children’s acquisition two or more language at the same time at the early age to find out the brain function in children. This data is descriptive which means that bilingualism & first language acquisition (BFLA) or second language acquisition (SLA), to refer to situations where the child’s exposure two or more languages begins at birth. This research at the qualitative research because it's appropriate systematically, factually, and accurately about language acquisition. This study uses theories in various data source that contains to languages as tool of communication for children’s ability and how brain works effect in children acquisition on thinking and the important things are psycholinguistics as the study of scientific between human and mind, and language as a tool of communication for children’s ability in thinking and processes the two or more languages as the assistance of living, where the experts of the theory will be provide in this researcher.